2019
DOI: 10.2147/ott.s229739
|View full text |Cite
|
Sign up to set email alerts
|

<p>MicroRNA-188-5p Promotes Epithelial–Mesenchymal Transition by Targeting ID4 Through Wnt/β-catenin Signaling in Retinoblastoma</p>

Abstract: Purpose: Here, we investigated the involvement of the miR-188-5p/inhibitor of the DNA binding 4 (ID4) axis in retinoblastoma (Rb). Patients and methods: We included 35 Rb tissues and the corresponding adjacent normal tissues. RT-qPCR, Western blot, lentivirus transfection, measurement of cell migration in vitro, and chip analysis were performed during the study. Mouse Rb models were established to investigate the in vivo mechanisms. Results: We showed that miR-188-5p was upregulated in Rb tissues; moreover, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…miR-125b promoted tumor growth and suppressed apoptosis by targeting DRAM2 in RB [22]. miR-188-5p promoted epithelial-mesenchymal transition via targeting DNA binding 4 through Wnt/β-catenin signaling in RB [23]. These studies indicate that abnormal miRNA expressed may have some influence on the development of RB.…”
Section: Introductionmentioning
confidence: 79%
“…miR-125b promoted tumor growth and suppressed apoptosis by targeting DRAM2 in RB [22]. miR-188-5p promoted epithelial-mesenchymal transition via targeting DNA binding 4 through Wnt/β-catenin signaling in RB [23]. These studies indicate that abnormal miRNA expressed may have some influence on the development of RB.…”
Section: Introductionmentioning
confidence: 79%
“…Many miRNAs have been reported to be abnormally expressed in RB, like miR-192, miR-34a and miR-376a (34)(35)(36)(37). In RB, miR-188-5p promotes epithelialmesenchymal transition by targeting DNA binding 4 via Wnt/β-catenin signaling pathway (38). This study screened DEMs in RB samples in comparison to nontumor retina samples.…”
Section: Discussionmentioning
confidence: 99%
“…Yun et la found that miR-188 directly targeted PTEN to affect Wnt/β-catenin signaling in gastric cancer [38]. Yang et al demonstrated that miR-188 significantly promoted EMT by down-regulating DNA binding 4 through Wnt/β catenin signaling in retinoblastoma [39]. The difference in these studies indicated that miR-188 might regulated Wnt/β-catenin signaling through different molecules in different cancer types.…”
Section: Discussionmentioning
confidence: 99%